1992
DOI: 10.5980/jpnjurol1989.83.1138
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Penile Necrosis in a Patient With Diabetes Mellitus

Abstract: The patient was a 63-year-old male who was with having diabetes mellitus since 1967. Hemodialysis was carried out from June 1983 for diabetic nephropathy. Neuropathy and retinopathy were already present at that time. He complained pain in penile glans from the middle of June 1990. Three month later, partial penectomy was performed because of the development of black-mummy-shaped necrosis on the whole glans. Histopathological examination widely revealed luminal obstruction and formation of thrombus due mainly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In retrospect, it is conceivable that treat ment with intravenous antibiotics and a more vigorous approach to establishment and maintenance of euglycemia may have facilitated resolution of unrecognized pe nile interstitial infection. On the other hand, as in the cases reported by Bour and Steinhardt [8], Nomura and Sakamoto [9], and Frydenberg [17], progression of penile necrosis, once begun, is uniformly rapid in severely ill patients. We were concerned by the outcome of one of the patients described by Bour and Steinhardt [8] who, during 'conservative' management of penile gangrene, lapsed into coma and died although under treatment with antibi otics.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In retrospect, it is conceivable that treat ment with intravenous antibiotics and a more vigorous approach to establishment and maintenance of euglycemia may have facilitated resolution of unrecognized pe nile interstitial infection. On the other hand, as in the cases reported by Bour and Steinhardt [8], Nomura and Sakamoto [9], and Frydenberg [17], progression of penile necrosis, once begun, is uniformly rapid in severely ill patients. We were concerned by the outcome of one of the patients described by Bour and Steinhardt [8] who, during 'conservative' management of penile gangrene, lapsed into coma and died although under treatment with antibi otics.…”
Section: Discussionmentioning
confidence: 60%
“…Blood to the dorsum of the penis and the glans is supplied by the dorsal artery [16]. What amounts to a vas cular network delivers a rich blood flow to the penis which, unlike fingers, toes, or entire lower limb, is spared [17] diabetic man with necrotic ulcers on extremities and neuropa thy developed penile gangrene which was treated with intrave nous antibiotics, but the entire penile shaft became necrotic, and total penectomy was performed: pathology revealed necro sis of penile shaft and dorsal penile artery with hyaline thicken ing of the wall and thrombus in the lumen; cultures were sterile Nomura and 1992 Japan 63 hemodialysis 7 Sakamoto [9] after 13 years of diabetes, complications of neuropathy, ne phropathy, and retinopathy were evident; the patient devel oped a mummy-shaped necrosis of the whole glans over 3 months which was treated with prostaglandins followed by par tial penectomy; histopathology revealed luminal obstruction by thrombus Both patients were subjected to penile amputation because of unrelenting penile ischemia and gangrene of the penile shaft despite antibiotic treatment for purported though minimally symptomatic bacterial infection. Nei ther patient had the perineal infection that defines Four nier's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, severe ischemia or necrosis of the glans penis is rare, and commonly due to circumcision, trauma, penile strangulation and administration of vasoconstrictive solutions 1,3 . Additionally, there are several pathologies which cause glanular ischemia or necrosis in adults, including diabetes mellitus, acute arterial occlusion, foreign bodies, Fournier's gangrene, spider bite and topical treatment with 1% gentian violet 4–8 . Ischemia of the glans penis following circumcision commonly results from dorsal penile nerve block with local anesthetics and inadequate surgical technique or devices 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Broughton 4 reported that hyperbaric oxygen and methylprednisolone treatment was an effective treatment for a patient with glanular skin necrosis due to spider bite. On the other hand, penile necrosis in patients with diabetes mellitus and Fournier's gangrene may need aggressive surgical debridement and partial penectomy following hyperbaric oxygenation 5,6 . Espana et al 2 .…”
Section: Discussionmentioning
confidence: 99%